How is implementation research applied to advance health in low-income and middle-income countries? - Alonge, Olakunle (BMJ Glob Health, 2019)
This paper examines the characteristics of implementation research (IR) efforts in low-income and middle-income countries (LMICs) by describing how key IR principles and concepts have been used in published health research in LMICs between 1998 and 2016, with focus on how to better apply these principles and concepts to support large-scale impact of health interventions in LMICs. There is a stark discrepancy between principles of IR and what has been published. Most IR studies have been conducted under conditions where the researchers have considerable influence over implementation and with extra resources, rather than in ‘real world’ conditions. IR researchers tend to focus on research questions that test a proof of concept, such as whether a new intervention is feasible or can improve implementation. They also tend to use traditional fixed research designs, yet the usual conditions for managing programmes demand continuous learning and change. More IR in LMICs should be conducted under usual management conditions, employ pragmatic research paradigm and address critical implementation issues such as scale-up and sustainability of evidence-informed interventions. This paper describes some positive examples that address these concerns and identifies how better reporting of IR studies in LMICs would include more complete descriptions of strategies, contexts, concepts, methods and outcomes of IR activities. This will help practitioners, policy-makers and other researchers to better learn how to implement large-scale change in their own settings.